Program “Pasien PANDAI” untuk Meningkatkan Optimisme Pasien Kanker - Rahmah Saniatuzzulfa; Sofia Retnowati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
The benefits of Pasien "PANDAI Program" (Patient with Acceptance and Action) for patient are to help them internalize self-acceptance toward their condition, give them peacefulness mentally, help them think of purposes in dealing with their illness, build a commitment to change their life to be better, and implement this commitment as a process of behavior change. The method used in this research was one group pretest-posttest design with 3 participants as experimental group. Wilcoxon SignedRank was used in quantitative analysis and supported by qualititave analysis using descriptive analysis. The result showed no difference between pretest-posttest (z=-0.447; p>0.05) and also posttest-follow up (z=-1.342; p>0.05). It indicated that Pasien PANDAI Program wasnn't effective to improve optimism in patient with cancer.